Predicting Heart Disease using Logistic Regression - Anshori, Mochammad; Haris, M. Syauqi (Knowledge Engineering and Data Science, 2022)
A common risk of death is caused by heart disease. It is critical in the field of medicine to be able to diagnose cardiac disease in order to adequately prevent and treat patients. The most accurate method of prediction has the potential to both extend the patient's life and reduce the severity of their cardiac disease. The use of machine learning is one approach that may be taken to generate predictions. In this study, patient medical record information was used in conjunction with an algorithm for logistic regression in order to make heart disease diagnoses. The outcomes of the logistic regression have been utilized to achieve a high level of accuracy in the prediction of heart disease. To get the model coefficients needed for the equation, the experiment uses an iterative form of the logistic regression test. Iteration 14 produced the best results, with an accuracy of 81.3495% and an average calculation time of 0.020 seconds. The best iteration was reached at that point. The percentage of space that lies beneath the ROC curve is 89.36%. The findings of this study have significant implications for the field of heart disease prediction and can contribute to improved patient care and outcomes. Accurate predictions obtained through logistic regression can guide healthcare professionals in identifying individuals at risk and implementing preventive measures or tailored treatment plans. The computational efficiency of the model further enhances its applicability in real-time decision support systems.